Barley farmland harbors a highly homogeneous soil bacterial community compared to wild ecosystems in the Qinghai-Xizang Plateau - Wang, Xiaolin; Yang, Yibin; Nan, Qiong; Guo, Jian-Wei; Tan, Zhiyuan; Shao, Xiaoming; Tian, Changfu (Frontiers in Microbiology, 2024)
Understanding patterns and processes of microbial biogeography in soils is important for monitoring ecological responses to human activities, particularly in ecologically vulnerable areas such as the Xizang Plateau. Highland barley is the staple food of local people and has mainly been cultivated along the Yarlung Zangbo River valley. Here we investigated soil bacterial communities from 33 sampling sites of highland barley farmland in this region and compared them to those from wild ecosystems including alpine tundra, meadow, forest, and swamp. In contrast to soils of wild ecosystems, these farmland samples harbored a highly homogeneous bacterial community without significant correlations with geographic, elevation, and edaphic distances. Discriminant bacterial taxa identified for farmland samples belong to Acidobacteria, with Acidobacteria Gp4 as the dominant clade. Although Acidobacteria were the most abundant members in all ecosystems, characterized bacterial taxa of meadow and forest were members of other phyla such as Proteobacteria and Verrucomicrobia. pH and organic matter were major edaphic attributes shaping these observed patterns across ecosystems. In contrast to other reports, pH and organic matter availability showed positive and negative correlations, respectively, with Acidobacteria abundance in tested samples. These findings provide an insight into the consequences of human activities and agricultural intensification on taxonomic homogenization of soil bacterial communities in the Xizang Plateau.